Soils of the rain forest in Central Guyana - Kekem, A.J. van (Tropenbos - Guyana Programme GeorgetownGY, 1996)
Presents results of a soil inventory carried out in the Mabura-Kurupukari area in Central Guyana. The area is part of a logging concession in which selected logging takes place. The survey seeks to provide base line data on which decisions regarding sustained use of the forest will be based.